Adhesion of Nano-ZnO Modified Asphalt and Its Influence on Moisture-Sensitive Properties of Mixtures - Xiaoming Chen; Ping Wen; Qibin Ji; Shujiang Jiang; Zhimin Zhou; Aipeng Wang; Lingyun Li; Bowen Guan (Advances in Materials Science and Engineering)
This study investigates the effect of nano-ZnO on modified asphalt’s adhesion characteristics by preparing various mixtures with 0%, 1%, 2%, and 3% nano-ZnO contents. Within the study context, the adhesion characteristics of asphalt mixtures with different nano-ZnO to limestone, basalt, and granite contents are studied using a boiling test. The surface-free energy (SFE) parameters of four asphalt and three aggregate types are evaluated using a theoretical approach and then verified by performing pull-off tests, and the adhesion work between different asphalt and aggregates is calculated. In addition, the effect of nano-ZnO on moisture-sensitive properties of the asphalt mixture is assessed using a freeze-thaw split test and semicircle bending (SCB) test. The study results have shown that nano-ZnO can enhance adhesion characteristics of the asphalt. The surface energy of modified asphalt with high ZnO content is relatively larger, and the adhesion between asphalt and limestone is better than the basalt and granite. The aggregates’ chemical composition and the SFE’s parameters significantly affect the adhesion between asphalt and aggregates. Furthermore, the correlation between the surface-free energy theory and the pull-off test results is better than the boiling test ones. Nano-ZnO enhances the asphalt mixture’s moisture sensitivity before and after freeze-thaw cycles and impacts the initial state’s tensile strength and cracks resistance, especially after freeze-thaw cycles where the improvement is obvious.